Pentingnya Pendidikan Karakter Pada Peserta Didik Sekolah Dasar Di Era Digital Untuk Meningkatkan Kualitas Pendidikan - Candra Kristiyan; Arri Handayani; Dini Rakhmawati (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The purpose of this article is to understand how important character education is for primary school students in the digital age. The phenomenon that occurs at this time is that students become easier to access information, thus causing the behavior of students who experience poor behavior. Because of that, education in Primary School needs to be balanced with character education. Character education is a process of moral and religious instillation that is given to students by way of teaching from now on, strengthening and behavioral development. The purpose of this article is to describe the education of the digital revolution era, to describe the importance of character education for Primary School students in the digital era and to describe how to implement the character education of Primary School students to face the digital era. The results of this study show that character education is important to show the degradation of character, morals and character in the digital age, so character education should be determined from today.